1D Nanoconfined Ordered‐Assembly Reaction. Issue 8 (6th March 2019) - Liu, Shijie; Zhang, Xiqi; Jiang, Lei
Abstract: 1D nanoconfined chemical reactions generally exhibit enhanced performance, as a consequence of nanoconfinement, yet the inherent mechanism of this nanoconfinement‐enhanced performance remains elusive. Here, the authors' perspectives on 1D nanoconfined chemical reactions are first provided, followed by the 1D nanoconfined preassembled reactions. Then, ultrafast mass transport behaviors in biological and artificial nanochannels are discussed and the quantum‐confined superfluid concept is introduced. Inspired by the programmed‐assembly reaction in living organisms, a new concept of ordered‐assembly reaction is proposed through combining quantum‐confined superfluid with frontier molecular orbital theory, to understand the inherent mechanism of high‐performance 1D nanoconfined chemical reactions. Finally, the prospective for future development of the ordered‐assembly reaction concept is presented. Abstract : Perspectives on 1D nanoconfined chemical reactions are discussed mainly focusing on organic syntheses and polymerization, followed by 1D nanoconfined preassembled reactions. A new concept of ordered‐assembly reaction is proposed, by combining quantum‐confined superfluid with frontier molecular orbital theory, to understand the mechanism of 1D nanoconfined chemical reactions, which will lead to highly efficient syntheses of chemical and biological molecules.